If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -6(-2x + -6) = 109 Reorder the terms: 1 + -6(-6 + -2x) = 109 1 + (-6 * -6 + -2x * -6) = 109 1 + (36 + 12x) = 109 Combine like terms: 1 + 36 = 37 37 + 12x = 109 Solving 37 + 12x = 109 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-37' to each side of the equation. 37 + -37 + 12x = 109 + -37 Combine like terms: 37 + -37 = 0 0 + 12x = 109 + -37 12x = 109 + -37 Combine like terms: 109 + -37 = 72 12x = 72 Divide each side by '12'. x = 6 Simplifying x = 6
| R^2+12r-66=-6 | | -4/7=?/28 | | ln(7x)=81 | | (X+2)-4-6x=3x+10 | | 91=-7(7-4k) | | 14=z-y | | -5n-7=23 | | Cosx=2sinx | | -6-6x=1x+4 | | 14a^2+7a-196=0 | | 355=-5n-5(8n-8) | | 2cos^2x+5sinx-5=0 | | 1/9=?/45 | | (X+2)-2(4-3x)=2(x+4)-4 | | (-7)-x=-5 | | 9n^2+94n-168=0 | | 7x-8=55-2x | | (-3)-x=2 | | p-12=218 | | .5x^2=8 | | -6a=36a | | y=2x-5x+7 | | 2.9r=-5.7t-5 | | x-(-14)=-11 | | 5y-9=7+y | | 60-what+10=20 | | 5=1-4(-5) | | 3m-7=m-13 | | 3x+9x+5=17 | | 4-5p=8 | | 2(X+8)+5x-9=3(X+2)+4(2x+9)-5(3x+8)+25-12x | | 3x^2=89 |